Ukrainian Identity Development in the Education System in the Conditions of Martial Law in Ukraine - Trubavina, Iryna; Cherednychenko, Oleksandr; Oliinyk, Nadiia; Nedria, Kirill (Educational Challenges, 2023)
The article is devoted to the actual problem of modern Ukrainian pedagogy – the national identity development. The purpose of the article is to identify the peculiarities of the national identity development in education in the conditions of war and to suggest the ways to strengthen this process. The research methodology is systemic, activity, cultural, axiological approaches. Research methods are: theoretical analysis of sources, generalization of experience, synthesis. Results. The Ukrainian identity is the result of national-patriotic education and a component of national security. The peculiarities of the national identity development in the Ukrainian system of education in martial law are revealed: the need for simultaneous development of Ukrainian and European values, attention to the value of life and continuing education in war, respect for human rights. The ways to strengthen the national identity development in the education system include are: official restoration of educational function of teachers in all regulatory documents; emphasis on education which is based on national and European values; teaching educators to perform their new functions – security function, information function, social assistance, social education of parents and the community; official clarification in regulatory documents of the definition of educators’ security function; normalization of the definition of a safe educational environment in martial law; introduction of the Declaration of School Safety into the education system, the Ukrainian Charter of a Free Person into the education system; the participation of students in volunteer activities; compliance of all stages of the educational process with the idea of national identity formation. Conclusion. The peculiarities of the national identity development and the ways to strengthen the national identity development today are very important. The prospects for further research are to identify the effectiveness of new ways of the Ukrainian identity development.